Bimbingan Awal Kewirausahaan pada Anak Usia Dini - Nurhafizah Nurhafizah (Jurnal Konseling dan Pendidikan)
Entrepreneur education should be started in early-childhood start from introduction stages then be an entrepreneur agent. It is taught to children to be mentally an entrepreneur. Due to this activity which is design to support their business. The students began to comprehend themselves, control their emotion and stress, time management, flexible communication, and decision maker. Developing student's entrepreneur mentality increases the students’ characteristic and behavior, responsibility towards an entrepreneur theoretical and practically, which is taken the long term period process.